Novice Teachers Challenges in Teaching and Learning Practice: Experiences of Elementary School Teachers in Makassar - Ridwan, Nurul Haeriyah (Al Hikmah: Journal of Education, 2022)
This study discusses the perceptions of novice teachers related to the challenges they experience in teaching and learning practices. Furthermore, teachers play an important role in education. This researcher aims to; 1) To find out the perception of novice teachers about what makes a good teacher, 2) To find out the challenges of novice teachers in teaching and learning practices in Makassar, 3) To find out how novice teachers overcome the challenges they experience in teaching and learning practices in Makassar. This study will apply a qualitative research design where the researcher will use open-ended questions to achieve the objectives of this study. research. Participants will be selected using purposive sampling technique. the criteria for the participants who were recruited were those who had taught less than 5 years in Makassar. Researchers conducted observations, interviews and document analysis to collect data. This study uses qualitative data analysis techniques to analyze the data, the steps are classified as follows; 1) Data Condensation, 2) Data Display, 3) Drawing and Verifying Conclusions. The findings show that novice teachers face challenges, namely 1) Lack of methods; 2) the naivety of elementary school students; 3) Lack of experience; 4) Pandemic, although three of them have never attended training, and the other two participants have attended one before, either organized by the ministry of religion or the school itself.